2022
DOI: 10.3389/fpls.2022.855858
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Water Availability on Leaf Trichome Density and Plant Growth and Development of Shepherdia ×utahensis

Abstract: Many arid lands across the globe are experiencing more frequent and extreme droughts due to warmer temperatures resulting from climate change, less predictable precipitation patterns, and decreased soil moisture. Approximately 60–90% of household water is used for urban landscape irrigation in the western United States, necessitating the establishment of landscapes using drought-tolerant plants that conserve water. Shepherdia ×utahensis (hybrid buffaloberry) is a drought-tolerant plant with dense leaf trichome… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
20
0
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 26 publications
(21 citation statements)
references
References 67 publications
0
20
0
1
Order By: Relevance
“…Chen, et al . 49 reported that relationship between leaf reflectance, trichome density and epidermal cell size/density, might indicate changes in cell size. It could be concluded that trichome density predominantly controls leaf reflectance in different environmental conditions.…”
Section: Discussionmentioning
confidence: 99%
“…Chen, et al . 49 reported that relationship between leaf reflectance, trichome density and epidermal cell size/density, might indicate changes in cell size. It could be concluded that trichome density predominantly controls leaf reflectance in different environmental conditions.…”
Section: Discussionmentioning
confidence: 99%
“…Similar findings were also reported by Yadav et al [ 72 ] who reported an increase in trichome length with an increase in the concentration of drought stress. Chen et al [ 87 ] also discussed the densities of leaf trichomes in relation to the availability of water and its effects on plant growth and development in terms of increased cell size and expansion in the leaf area.…”
Section: Discussionmentioning
confidence: 99%
“…In summary, changing trichome size (length and width) is a signi cant adaptation to cope with changes of temperature in different environmental. Chen, et al 49 reported that relationship between leaf re ectance, trichome density and epidermal cell size/density, might indicate changes in cell size. It could be concluded that trichome density predominantly controls leaf re ectance in different environmental conditions.…”
Section: Discussionmentioning
confidence: 99%